Adverse pregnancy outcomes and future maternal cardiovascular disease - Hauspurg, Alisse; Ying, Wendy; Hubel, Carl A.; Michos, Erin D.; Ouyang, Pamela (Clinical cardiology (Mahwah, N.J.), 2018)
Cardiovascular disease (CVD) remains the leading cause of death in women. Although traditional risk factors increase later‐life CVD, pregnancy‐associated complications additionally influence future CVD risk in women. Recent guidelines for the prevention of CVD in women have added adverse pregnancy outcomes as major CVD risk factors. Studies have shown that women with a history of preeclampsia, gestational diabetes, preterm delivery, and delivery of a small‐for‐gestational‐age infant have an increased risk of developing cardiometabolic risk factors and subsequent CVD. A history of multiple adverse pregnancy outcomes further increases this risk. It has been suggested that these pregnancy complications may unmask preexisting elevated CVD risk; however, whether the pathophysiologic changes underlying these conditions directly result in long‐term cardiovascular damage is unclear. The purpose of this review was to highlight the associations between adverse pregnancy outcomes and future CVD, and to emphasize the importance of considering pregnancy history in assessing a woman's CVD risk. Targeted efforts to initiate screening and risk‐reduction strategies in women with prior history of pregnancy complications, particularly lifestyle modification, may help decrease the burden of CVD in women.